Error analysis in German writing by Chinese Malaysian students - Tan, Wan Ting (2016)
Transfer from a pre-existing linguistic repertoire to a target language is an important issue in foreign language acquisition. There are limited studies focusing on common German grammatical errors in the written form, both morphological and syntactical, that are made by Chinese Malaysian students in the Malaysia context. Furthermore, the correlation of these errors with structural differences between the students’ linguistic repertoire and the target language, i.e. German language should be given attention. The principal objective of this study is to ascertain the direct correlation between the influence of the students’ dominant language (Chinese) and the language of instruction (English) with the extent of grammatical errors made whilst acquiring the German language. Twenty Chinese Malaysian students participated in this study, and the data were collected from their compositions. The respondents were Chinese Malaysian students from the International Education College who have Chinese as their first language. The ungrammatical structures found in the written compositions of the students were analysed. This study used Contrastive Analysis to examine the differences between Mandarin Chinese, English and German. Error Analysis was used to identify the errors that had been made by the participants. This study was designed by the author based on the Interlanguage Theory. Common grammatical errors were categorised and analysed. The research findings prove that the learners were confused by the difficulties in German grammar. The study also reveals that the sources of errors were also intralingual and not just interlingual. Error Analysis provides information on the effectiveness of the teaching and the weakness of the participants. The results also reveal errors other than grammatical errors which should be given attention by the instructors or academics. The findings can help to enhance the teaching and learning of German as a foreign language in a class attended by learners who have Chinese and English as their previously acquired languages. This study also provides an insight into the nature of the learners’ erroneous sentence construction.